PUBLIC POLICIES, INTELLECTUAL PROPERTY AND CREATIVE ECONOMY - Gutiérrez Ocegueda, Gelacio Juan Ramón; Aceves, Edgar Gutiérrez (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction. I.- The Origins of Studies on Agenda Formation and Public Problems. Ii.- The Formation of Agendas Like Object of Study of Political Science. Iii.- What They are and How Agendas are Formed. Iv.- The Institutional Variable. V.- The Effectiveness and Efficiency as Distinctive Signs of Policies Public. Vi.- The Decision-Making Process of Public Policies. Vii.- The Adaptability of Public Policies in Contexts Different. Viii.- Differences that the Concepts Keep Between Each Other Polity, Politics and Policy from The Disciplinary Side Of Public Politics. Ix.- Approaches And Distances Between Public Policies and Governmental Policies. X.- Policies Public, Democracy and Governance. Xi.- The Flow of Policies Public. Xii.- Steps for the Analysis of Public Policies. Xiii.- The Political in Different Properties. Xiv.- Public Policies, Intellectual Property nd Creative Economy. Conclusions. Bibliography.